2022
DOI: 10.4102/hts.v78i4.7172
|View full text |Cite
|
Sign up to set email alerts
|

The effect of religiosity on life satisfaction: A meta-analysis

Abstract: This article intends to synthesise the results of various studies related to the influence of religiosity on life satisfaction, with the aim of mapping how religiosity variables influence people’s life satisfaction in multiple countries. Additionally, this study seeks to identify the development of research issues regarding religiosity and life satisfaction. For this reason, a meta-analysis approach was applied to synthesise 21 articles quantitatively, and the systematic literature review (SLR) approach was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…In addition, previous studies reveal that when employees show commitment to the empirical and theoretical fundamentals of the religion (religiosity), they demonstrated positive feeling and attitude such as life satisfaction (Sholihin, Hardivizon, Wanto, & Saputra, 2022), job satisfaction (Achour et al, 2015;Tiliouine & Belgoumidi, 2009), higher well-being (Hoogeveen et al, 2022, less anxiety (Abdel-Khalek, 2010) and stress (Kandaswamy, 2007). Moreover, researchers have continuously argue that employee characteristic to have an influence on motivation to transfer (Cheng & Hampson, 2008;Gegenfurtner et al, 2009b) and motivation to learn (Ayres, 2005;Mathieu & Martineau, 1997).…”
Section: The Relationship Between Religiosity Motivation To Transfer ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous studies reveal that when employees show commitment to the empirical and theoretical fundamentals of the religion (religiosity), they demonstrated positive feeling and attitude such as life satisfaction (Sholihin, Hardivizon, Wanto, & Saputra, 2022), job satisfaction (Achour et al, 2015;Tiliouine & Belgoumidi, 2009), higher well-being (Hoogeveen et al, 2022, less anxiety (Abdel-Khalek, 2010) and stress (Kandaswamy, 2007). Moreover, researchers have continuously argue that employee characteristic to have an influence on motivation to transfer (Cheng & Hampson, 2008;Gegenfurtner et al, 2009b) and motivation to learn (Ayres, 2005;Mathieu & Martineau, 1997).…”
Section: The Relationship Between Religiosity Motivation To Transfer ...mentioning
confidence: 99%
“…To date, no study has been identified to address such relationships, particularly on the effect of religiosity on motivation to transfer and motivation to learn. Most of previous studies have focused on examining the impact of religiosity on another aspect of human resources such as job performance (Osman-Gani, Hashim, & Ismail, 2013), work values (Yeganeh, 2015), employees' well being (Achour & Boerhannoeddin, 2011), commitment (Imran, Abdul Hamid, & Aziz, 2017), organizational citizenship behavior (Darto, Setyadi, Riadi, & Hariyadi, 2015) and life satisfaction (Sholihin, Hardivizon, Wanto, & Saputra, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising because religiosity is a difficult term to be defined (Gill, Minton & Myers 2010). Sholihin et al (2022) stated that this happens because the definition given will tend to depend on the assumptions that it is according to the religious perspective adopted. That is the reason why there are several different views commonly known.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Individuals who are considered satisfied with life feel happiness and a sense of well-being. Correspondingly, Sholihin et al (2022) stated that individual life satisfaction can be described as the feeling of happiness possessed by individuals when they achieve the desired level of well-being. Maksum and Indahwati (2021) mentioned that the variable 'life satisfaction' refers to the extent to which individuals feel happy and free from the pressures of life that cannot be controlled.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation